2016
DOI: 10.1007/s00192-016-3149-7
|View full text |Cite
|
Sign up to set email alerts
|

De novo stress urinary incontinence after pelvic organ prolapse surgery in women without occult incontinence

Abstract: The incidence of de novo SUI after surgery for POP without occult SUI was 9.9 %. We recommend counseling patients about the risk of de novo SUI and offering a staged procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 26 publications
6
39
1
Order By: Relevance
“…In the present series, the addition of anterior repair to high USL suspension did not result in a reduction of the POSUI rate. This finding is consistent with the report by Alas et al., who found that anterior repair did not have a protective role.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present series, the addition of anterior repair to high USL suspension did not result in a reduction of the POSUI rate. This finding is consistent with the report by Alas et al., who found that anterior repair did not have a protective role.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous studies: Lensen et al . identified self‐reported SUI as the most important predictor of POSUI, and Alas et al . found that non‐occult SUI at baseline was a risk factor for POSUI.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, there is scanty data about the efficacy and safety of this combined surgical approach in women with stress urinary incontinence [17-19]. …”
Section: Introductionmentioning
confidence: 99%